The Oligocene Equisetum from Qaidam Basin, Northeastern Tibetan Plateau in China and its implications. (2nd November 2021) - Chen, Hong-Yu; Yang, Tao; Han, Lei; Wang, Yong; Wang, Hao-Jian; Bao, Lin; Li, Wen-Jia; Cai, Jia-Hao; Liang, Wei-Yu; Dai, Yan-Zhi; Zhang, Li; Xie, San-Ping; et al.
ABSTRACT: Equisetum: (Equisetaceae, Equisetales) is widely distributed around the world and distinguished by obviously jointed stems with longitudinal ridges or furrows. Recently, fossil materials collected from the Shangganchaigou Formation of northwestern Qaidam Basin, China, are assigned to Equisetum based on the presence of jointed stems, longitudinal ridges, and whorls of branch scars. The current specimens are the first discovery of Equisetum in northern Tibetan Plateau and also represent the first fossil record of the genus from Oligocene in Qaidam Basin. The new discovery enriches the knowledge of the paleo-diversity of the Equisetum and indicates that the sphenophytes once existed in the northern Tibetan Plateau. Based on the fossil records in and around the Tibetan Plateau, Equisetum could survive at a higher latitude during the Palaeogene and they could only grow in lower latitude since the Neogene, which might be the result of the tectonic deformation and climatic changes in the northern plateau since the Miocene. The current fossil, together with co-existed fossils, indicate that there have been rich drainages and temperate deciduous broad-leaved forest with grass in northwestern Qaidam Basin during the Oligocene.